Orchid resilience : A case of a logged-over forest in Sabah, Malaysia - Siti Fatimah, Md Isa; Meery, Nior; Harniza Izzati, Razali; Elia, Godoong; Nor Azizun, Rusdi; Hamzah, Tangki; Akmal, Raffi (Malaysian Nature Society, 2023)
Taliwas River Conservation Area (TRCA) is a lowland dipterocarp forest located 36km from Lahad Datu town. The area was logged in the 1970s by forest concessions and was treated with silvicultural practices for restoring ecosystems and conserving biodiversity. TRCA is one of the earliest logged forest that been treated with silvicultural activities and enriched with dipterocarps trees. This study was aimed to evaluate the species diversity of orchids in treated logged-over forest of TRCA. Convenience sampling was conducted due to the orchids’ sporadic distribution pattern. The orchids were photographed and all morphological features were documented for further identification. A total of 45 species were identified to their respective genera, with 16 genera recognised as epiphytic orchids, three as terrestrial, one as lithophyte and one as climber. From this study, orchid species was shown to be remarkably resilient in logged forest, through their advance morphological features such as pseudobulb, seed dormancy and epiphytic growth habit. The results from this study can be used as baseline data to support conservation and development plan of the Taliwas logged-over forest area.